Meningkatkan Kesadaran Menabung Anak Usia Dini Di SD Negeri 56 Perumnas Poka Ambon - Ronald D. Hukubun; Valentine D. Saleky; Eva S. Ratuluhain; Albert F. Thomas; Alvind G. Kambuno; Febiyanty Palijama; Riski A. K. Rumata; Shinta Syaranamual (Lembaga Pengembangan Kinerja Dosen, 2024)
Early savings socialization for students of SDN 56 Perumnas Poka is an effort to teach students about the importance of early savings. This socialization program is useful to provide students with an understanding of how to set aside money, manage money, and introduce the concept of saving. In this program, students are taught about the importance of saving through activities. They are given an understanding of the purpose of saving, such as to prepare for the future or for emergency needs. This socialization activity is carried out using a method in implementing this socialization activity by providing and educating students about the importance of saving and also giving lessons on the benefits of saving since childhood, and practice making piggy banks from used materials. With this socialization program, it is hoped that elementary school students at SDN 56 Perumnas Poka can understand the importance of managing money well and must have the habit of saving from an early age. This will help them increase their awareness of saving money from an early age to build their future.